Studying Inhibitory Effect of William Pear and Propolis against Alernaria Alternate with Diagnosis of Some Active Compounds - Mohammed Allawi (Journal of Global Pharma Technology, 2016)
Alternaria alternate was isolated from orange juice, using potato dextrose agar (PDA) media, incubated for 5 days at 27 co, the evaluating anti fungal effects were seven different concentration (1.25, 2.5, 5, 10, 15, 20, 25) mg / ml of the extract alcohol: (William pear extract = WPE) and (Propolis extract = PE), the inhibitory efficacy of each extract against the fungus was increased by increasing its concentration. Also observed that the inhibitory activity of (PE) was greater than (WPE).The separation process of (PE) showed a presense: Flavone, 3-hydroxy flavone and Quercetin and absense these compounds in (WPE).Keywords: Propolis, Wiliam pear, A. alternate, TLC.